Caio Fernando Abreu por Caio F. - Kogure, Linda Emiko (2015)
This paper aims to analyze the literally work of Caio Fernando Abreu (CFA) through the self written perspective (auto or/and alterfictional) and performance, from two point of views: first from the “travelers” (in permanent deployment from de characters in proximity to the author’s trips) and the other from the personae, mainly, the ones seen in the letters where CFA “shuffles in” other selves, signing different names, such as Caio F. The structure is analog to a travel script, the two point of views studied culminate in a travel log, with novels, tales, letters, “chronicles” and interviews fragments from the author to newspapers and magazines. The travel log is signed by Caio F., the other self that triumphs as a trace of a trace, the literally symbol, the representative, the most iterated persona that substitutes or overlaps more and more the author’s name, even after over three decades from its creation.